Influência de doses de fósforo e de cultivos sucessivos nos níveis de frações de fósforo inorgânico, na presença ou ausência de vegetal - Gonçalves , José Antônio; Braga , José Mário; Castro Bahia Filho , Antônio F (Revista Ceres, 2025)
This study is based on Bahia Filho’s data as well as on chemically analyzed soil samples collected after each period of cultivation in order to obtain inorganic phosphorus fractions.